Meta-analysis of genome scans and replication identify CD6, IRF8 and TNFRSF1A as new multiple sclerosis susceptibility loci - De Jager, Philip L; Jia, Xiaoming; Wang, Joanne; de Bakker, Paul I W; Ottoboni, Linda; Aggarwal, Neelum T; Piccio, Laura; Raychaudhuri, Soumya; Tran, Dong; Aubin, Cristin; Briskin, Rebeccah; Romano, Susan; et al. (Nature genetics, 2009)
Philip De Jager and colleagues report results of a large genome-wide association and replication study for multiple sclerosis. The work uncovers three new susceptibility loci for MS, including common and rare variants at TNFRSF1A and common variants at IRF8 and CD6 . We report the results of a meta-analysis of genome-wide association scans for multiple sclerosis (MS) susceptibility that includes 2,624 subjects with MS and 7,220 control subjects. Replication in an independent set of 2,215 subjects with MS and 2,116 control subjects validates new MS susceptibility loci at TNFRSF1A (combined P = 1.59 × 10 −11 ), IRF8 ( P = 3.73 × 10 −9 ) and CD6 ( P = 3.79 × 10 −9 ). TNFRSF1A harbors two independent susceptibility alleles: rs1800693 is a common variant with modest effect (odds ratio = 1.2), whereas rs4149584 is a nonsynonymous coding polymorphism of low frequency but with stronger effect (allele frequency = 0.02; odds ratio = 1.6). We also report that the susceptibility allele near IRF8 , which encodes a transcription factor known to function in type I interferon signaling, is associated with higher mRNA expression of interferon-response pathway genes in subjects with MS.